Frio frozen fruit delights - Castro, John Amar; Estadilla, Marc Joseph; Latagan, Salvacion; Obenita, Mylene
People nowadays are inclined in different healthy choices. Many are motivated to join hosted marathons; some prefer to engage themselves in a healthy diet. In this increasing awareness on healthy living, many small to medium enterprises are introducing varying types of healthy concoctions and desserts in the market. These beverages or desserts range from a simple fruit shake to pricey frozen yoghurts. Though there are many choices, these products seem to be the same, offering same taste and experience. And with high prices on products of the major players, many individuals are searching for an alternative that is unique, yet still healthy, and affordable. Given these factors, FRIO is a company that shall give these products and services to those who are venturing themselves on a healthy living on a budget. Frio-Frozen Fruit Delights, is a local company aimed to provide healthy concoctions and integrate the cozy experience that many urban and sub-urban consumers are searching for. Fruitty Frappe is the primary product of the company which is composed of the regular fruit shake, mixed with varying toppings and cereals, and topped with a whipped cream. Aside from the Fruity Frappe, other products wilt be offered: Fruit Loose, a typical fruit shake, and Sundae Gleez, a sundae ice cream topped with fresh fruits. These products are priced strategically and are based on customer preferences. The essential factor for a product to be successful is its market feasibility. A survey was conducted in Bulacan, a province situated north of Metro Manila, to check the taste of the probable consumers. This area has been pre-selected since it has a market population similar to Metro Manila and the healthy concoctions industry is not yet saturated. The survey shows that 79% of the respondents are willing to buy the product. To reach out these prospect customers, marketing efforts will be pursued using the local print advertisements and free social networking sites. Initially, FRIO will put up its first branch in the infamous SM City Marilao, located in Southern Bulacan. This commercial center is very attractive to both business entrepreneurs and consumers as the facility is accessible and complete with the facilities that shall provide high quality services. In addition to the business location, sourcing of raw materials, equipment and machines are also important. These are readily available in the area and shall boost the local market. To deliver the products to consumers, the process of producing the products is well crafted and is benchmarked on the procedures employed by other companies. The company is also concerned on environmental issues. In line with this, packaging materials are mostly from biodegradable products and an appropriate waste management system will be imposed. Establishment of FRIO requires an initial capital of Php 450,000 pesos that can be sourced in the local credit cooperative. This investment can be recovered in almost 2.5 years and loans are repaid in 3 years, suggesting that the project is profitable. Aside from financial benefits that the company can contribute to the local government, FRIO will provide jobs to Bulakenyos. it will offer convenience to customers by bringing to the Greater Metro Manila market the taste and experience of having healthy concoctions that are usually available in Manila.